The dynamics of both filamentous and globular mammalian reovirus viral factories rely on the microtubule network - Eichwald, Catherine; Ackermann, Mathias; Nibert, Max L. (Virology (New York, N.Y.), 2018)
Mammalian reovirus viral factories (VFs) form filamentous or globular structures depending on the viral strain. In this study, we attempt to characterize the dynamics of both filamentous and globular VFs. Here, we present evidence demonstrating that globular VFs are dynamic entities coalescing between them, thereby gaining in size and concomitantly decreasing in numbers during the course of the infection. Additionally, both kinds of VFs condense into a perinuclear position. Our results show that globular VFs rely on an intact MT-network for dynamic motion, structural assembly, and maintenance and for perinuclear condensation. Interestingly, dynein localizes in both kinds of VFs, having a role at least in large globular VFs formation. To study filamentous VF dynamics, we used different transfection ratios of µNS with filamentous µ2. We found a MT-network dependency for VF-like structures perinuclear condensation. Also, µNS promotes VFLSs perinuclear positioning as well as an increase in acetylated tubulin levels. •Filamentous and globular reovirus viral factories (VF) condense in perinuclear region.•Globular VFs coalesce among them.•The motion dynamics of both kinds of VFs rely on intact MT-network and dynein.•Intact microtubules are necessary for formation and maintenance of globular VFs.•µNS has a role in the positioning of filamentous VF like structures.